ANALYSIS OF FINANCIAL REPORTS USING TREND ANALYSIS METHOD TO EVALUATE FINANCIAL PERFORMANCE AT PT. BUKIT ASAM TBK PERIOD 2018-2022: ANALISIS LAPORAN KEUANGAN DENGAN METODE TREND ANALYSIS UNTUK MENGEVALUASI KINERJA KEUANGAN PADA PT. BUKIT ASAM TBK PERIODE 2018-2022 - DESMITA SARI; MUHAMMAD FAUZAN; SM. GUNTUR (Indragiri Research Center (ingreat), 2024)
This research was carried out at PT. Bukit Asam Tbk. The phenomenon that occurs can be seen from the financial reports. Profits and losses from 2018-2022 tend to increase. The aim of this research is to determine the condition of the company's financial reports and financial performance. The research method used is a quantitative descriptive method with secondary data sources. The data collection technique used is literature study, online data browsing and documentation. The research results show that the percentage generated for the profit and loss financial report on net income for the 2018-2019 period tends to increase, whereas in 2019-2020 it decreased, then in 2021-2022 it increased. The cost of revenue for the 2018-2019 period tends to increase, while in 2019-2020 it decreases, then in 2021-2022 it increases. Gross profit for the 2018-2020 period tends to decrease and for the 2021-2022 period there is an increase. Furthermore, operating profit in the 2018-2020 period decreased and in the 2021-2022 period it increased. This increase was due to the increase in mining service costs and royalty costs after the COVID-19 pandemic.